A Comparison of Three Geophysical Methods for Determining the Depth to Bedrock (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The location of the study site for the presented research here is at Illinois in USA. Geophysical investigations were conducted to characterize the subsurface. At the site, borehole control, downhole seismic (DHS), seismic refraction tomography (SRT) and multichannel analysis of surface waves (MASW) data were acquired for the purpose of seismic site characterization. Shear wave and compressional wave velocities were used to estimate depth to bedrock. The data analyses showed the depth to bedrock determined by DHS, MASW and SRT is in good agreement with borehole data.